Relationship between Teacher Work Motivation and Well-being at Different Stages of covid-19 Lockdown - Karamushka, Liudmyla; Kredentser, Oksana; Tereshchenko , Kira; Lazos, Gelena; Klochko , Alla (Social Welfare: Interdisciplinary Approach, 2021)
Based on empirical research, the authors show that the first wave of the COVID-19 lockdown (March – June, 2020) had some negative impact on teacher well-being, in particular on such its component as physical health and well-being. It has been found that the types of teacher work motivation have different relationships with teacher well-being at different stages of the COVID-19 lockdown. The authors substantiate the necessity of developing teacher autonomous work motivation, in particular its identified and integrated types, to promote teacher well-being during the COVID-19 pandemic.